“Some are guilty but all are responsible” – A.J. Heschel’s opposition to all forms of persecution - Szczerbiński, Waldemar (Studia Europaea Gnesnensia, 2023)
The main purpose of this article is to analyze racial persecution in the light of Heschel’s religious concept of equality. The Jewish thinker analyzes this problem based on the phenomenon of persecution of black people by the followers of monotheism in the United States, both by Jews and Christians. Heschel asks a fundamental question: How can a religious man persecute another man because of the color of his skin?